The Impact of Teachers' Questioning Skills on Students' Engagement in History Lessons in Haidian, People's Republic of China - Fang Chengfeng (Universitas Negeri Semarang, 2024)
The purpose of this study was to determine the influence of teachers' skills in asking questions of the activity of learning history in Haidian High School. Question skill is skill that used to got answer from others. Nearly the whole process of evaluation, measurement, assessment, and testing is done through questions. The results showed that grade history teacher skills in asked questions included in the medium criteria with a total score of 8559 the percentage gained an average of 47.02 (49%). Students' learning activeness class in Haidian High School about history with a total score of 8057 earned an average of 44.26 (49%) included in the medium category. Results of regression calculations obtained F value is 2244.782, As for determining the value of the Ftable on the degrees of freedom dfreg bla = 1 and dfres = n-2, the value Ftable by F (5%, 1, 180) = 3.89 From these calculations it appears that Fvalue greater than Ftable is 2244.782> 3.89, it can be said that Ho is rejected or there is a meaningful or significant relationship between teacher's skills in asked questions of the activity of learning history in class.